Prodevelopmental Orientation as a Determinant of an Active Cooperation of a Subject for the Benefit of Constructing One’s Own Career - Cybal-Michalska, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2012)
The orientation of a contemporary society towards a global career creates the need of rebuilding the frames of human activity and innovation. The most important is active participation and cooperation in a reality undergoing a permanent change. Conceptualization of quality new apprehension of career issues as an individual’s possession indicates a many-sided character of a contemporary discourse, which combines implications of an interdisciplinary dialogue and creates the need to review theoretical reflection about the way of understanding career and conditions, as well as indicators of its formation and construction. The „prodevelopmental orientation” is a remedy for a contemporary human being to be oneself again in this situation in the world of careers. In this attitude towards the definition of „a career”, one underlines importance of constructing (not choosing) a career for designing a quality of life.